Original method of posterior aortoplasty for aortic valve replacement in cases with narrow aortic ostium - V. V. Popov (Український журнал серцево-судинної хірургії, 2019)
132 patients with isolated aortic valve disease with narrow aortic ostium who underwent surgery in the Institute from 1 May 2009 to 01 Jan 2019 are included in the study group. Among 132 patients, 6 died at the hospital stage (hospital mortality – 4.5%). There were no negative remarks to the surgical technique in any case. Changes in echo data during the hospital stay: systolic pressure gradient across the left ventricular outflow tract (LVOT) before operation was 105.1±11.5 mmHg, with 25.9±4.1 mmHg on the aortic prosthesis upon discharge. Reconstruction of the root and ascending aorta according to the proposed method in cases of aortic hypoplasia and aortic valve replacement (AVR) is highly effective intervention.